Diseño de un sistema de gestión de energía eléctrica en la fábrica cartonera "GRUPO YARON" Aplicando la NORMA ISO 50001. - Ronquillo Moreta, Alex Fernando (2020)
Focusing on the policies implemented in Ecuador's constitution, aimed at improving the efficiency of energy consumption in Ecuador's industries, and energy diagnosis have been carried out for the "GRUPO YARON" cardboard factory using the ISO 50001:2018 standard to manage the efficient use and consumption of electrical energy. The cartonera company has two production areas. The first, in an area of 1600 m2 destined for the production of corrugated cardboard sheets of high graphic and structural quality for the vegetable and legume market. The second, with an area of 750 m2 destined for printing, folding and stapling of corrugated cardboard boxes, which has a total of 23 machines installed at 220 V three-phase with a steam boiler which supplying 120 psi diesel combustion pressure, two air compressors at 100 psi. Connected to 220 V three-phase, which identified as the section with the highest energy consumption, is the cardboard sheet processing section. In the development of the project, and energy diagnosis was applied, analyzing significant users of each type of energy and being able to categorize it, to present it as a savings opportunity to work on in order to make the process efficient. These performance indicators, evaluated in different types of energy, will allow a reduction in consumption and an improvement in efficiency, thus evidencing the effectiveness of the plans, actions, controls, and improvement opportunities implemented. Focusing on the guidelines of the ISO 50001 standard, improvement plans are established, such as awareness campaigns and training on the use and consumption of energy, operational control in the cardboard lamination and printing section. Helping to focus on reducing costs and consumption of electricity and fuel, which have currently increased.